Богдан Рідуш – палеогеограф, геоморфолог, геолог, палеотеріолог, археолог - Поп'юк, Яна (Novitates Theriologicae, 2022)
POPIUK, Y. Bogdan Ridush, a palaeogeographer, geomorphologist, geologist, palaeomammalogist, and archaeologist. — Bogdan Tarasovych is a well-known Ukrainian Quaternary palaeogeographer, a specialist in Quaternary megafauna, speleologist, Doctor of Geographical Sciences, Candidate of Historical Sciences, professor. His scientific interest in the field of mammalogy is mainly related to the study of cave sites of fossil fauna, as well as alluvial and loess. The main research is conducted in the regions of Bukovyna, Podillia, Carpathians, Northern Black Sea coast, and Crimea. He uses the remains of proboscideans for biostratigraphic dating of sections. He participates in international projects on paleoDNA of various groups of fauna. ПОП’ЮК, Я. Богдан Рідуш — палеогеограф, геоморфолог, геолог, палеотеріолог, археолог — Богдан Тарасович — відомий український палеогеограф квартеру, фахівець із четвертинної мегафауни, спелеолог, доктор географічних наук, кандидат історичних наук, професор. Наукова діяльність у галузі теріології пов’язана головним чином з дослідженням печерних місцезнаходжень викопної фауни, а також з алювіальними та лесовими. Основні дослідження проводить у регіонах Буковини, Поділля, Карпат, Пн. Причорномор’я, Криму. Використовує рештки хоботних для біостратиграфічного датування розрізів. Бере участь у міжнародних проєктах з вивчення палеоДНК різних груп фауни.